Insulin biosensor development: a case study§. Issue 1 (2nd January 2017) - Sanghera, Narinder; Anderson, Alexander; Nuar, Nick; Xie, Can; Mitchell, Daniel; Klein-Seetharaman, Judith
Abstract: Obesity is a major problem and maintaining a healthy diet and body weight has become increasingly important. Insulin is a known biomarker for the human metabolism, and measuring insulin may thus help inform decisions about diet choices. This provides a strong motivation to develop a fast, cheap, sensitive and easy to use home biosensor for insulin. Here we discuss the challenges and trade-offs between sensitivity, specificity, dynamic range, analysis times, instrumentation and sample transport and storage requirements for different biosensor development approaches. We show that the sensitivity of conventional SPR with a lower limit of detection of 0.5 nM is too low for practical purposes. Label-free antibody and aptamer carbon nanotube based systems suffer from lack of specificity. Highest sensitivity is afforded by mesoscale and phase monitoring electrochemical impedance spectroscopy assays with detection limits in the fM range, currently available only in a laboratory setting. Thus, a home-based insulin dip-stick is yet to be developed. Biosensing traces and structure of insulin: an important molecule to be quantified with role in obesity and diabetes: